Ecotoxicological evaluation of chemical indicator substances present as micropollutants in laboratory wastewaters - Silva, A. (2019)
Laboratories produce a large volume of wastewaters containing different chemical indicators, organic species for which there is no complete knowledge about their effects in the aquatic environment. The aim of this work was to evaluate the ecotoxicity of four chemical indicator substances commonly used in titrations (sodium diphenylamine-4-sulfonate, phenolphthalein, methyl orange, and eriochrome black T) by applying two distinct bioassays that evaluated the growth inhibition of the microalga Chlorella vulgaris and the acute immobilization of the microcrustacean Daphnia magna. All the indicators showed growth inhibition rates in the chronic test performed with the alga C. vulgaris. Only phenolphthalein and eriochrome black-T showed high immobilization rates on the acute test for D. magna. C. vulgaris showed higher sensitivity to the chemical indicators tested than D. magna. Eriochrome black T was the most toxic for both test organisms and, according to the effective concentration that causes inhibition on 50% of C. vulgaris population, it can be considered as “highly toxic to aquatic organisms”. Phenolphthalein and methyl orange may be classified as “toxic to aquatic organisms” and sodium diphenylamine-4-sulfonate is the least toxic, only being considered as “harmful”. This work increases the awareness of the hazardous effects of these chemical indicators and reinforces the need of improved solutions to manage and treat laboratory effluents.